2010
DOI: 10.1097/brs.0b013e3181cd656f
|View full text |Cite
|
Sign up to set email alerts
|

Low Back Pain in Primary Care

Abstract: Interventions designed to reduce high health care costs for LBP should focus on patients with severe LBP and depressive comorbidity. Our results add to the economic understanding of LBP care and may give guidance for future actions on health care improvement and cost reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
96
4
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(109 citation statements)
references
References 25 publications
6
96
4
3
Order By: Relevance
“…Including both direct and indirect costs, chronic pain imposes the greatest economic burden of any health condition (Ferrari & Russell, 2003; Stewart, Ricci, Chee, Morganstein, & Lipton, 2003). Persistent back pain in particular is one of the principal drivers of these costs, both in the U.S. (Becker, et al , 2010) and internationally (Hoy, et al , 2010), with indirect costs (e.g., lost or reduced work productivity) accounting for more than half of this economic burden (Phillips & Harper, 2011). In addition, the presence of a long-lasting pain syndrome is a leading risk factor for suicide, and psychosocial variables play crucial roles as risk factors or protective factors for suicidality in pain patients (Edwards, Bingham, Bathon, & Haythornthwaite, 2006).…”
Section: Background and Overview Of Pain Issuesmentioning
confidence: 99%
“…Including both direct and indirect costs, chronic pain imposes the greatest economic burden of any health condition (Ferrari & Russell, 2003; Stewart, Ricci, Chee, Morganstein, & Lipton, 2003). Persistent back pain in particular is one of the principal drivers of these costs, both in the U.S. (Becker, et al , 2010) and internationally (Hoy, et al , 2010), with indirect costs (e.g., lost or reduced work productivity) accounting for more than half of this economic burden (Phillips & Harper, 2011). In addition, the presence of a long-lasting pain syndrome is a leading risk factor for suicide, and psychosocial variables play crucial roles as risk factors or protective factors for suicidality in pain patients (Edwards, Bingham, Bathon, & Haythornthwaite, 2006).…”
Section: Background and Overview Of Pain Issuesmentioning
confidence: 99%
“…Although most patients recover completely within 4–8 weeks, a subset of patients is prone to develop chronic low back pain (CLBP). CLBP has become a major challenge for public health care systems worldwide [1]. The prevalence of CLBP is about 23%; around 12% of the afflicted patients are severely disabled [2], [3].…”
Section: Introductionmentioning
confidence: 99%
“…Available diagnostic tests are controversial [2, 3, 26, 27]. Although some authors insist on a strict separation of NRS and VAS [28], pain intensity was assessed using a combined scale in the ManRück study, which was shown to be both easy for patients to handle and precise for data analysis and calculations.…”
Section: Discussionmentioning
confidence: 99%
“…The high socioeconomic burden caused by the direct and indirect costs of LBP has often been described [3, 4]. More importantly, patients’ quality of life is markedly reduced.…”
Section: Introductionmentioning
confidence: 99%